PENGEMBANGAN MODUL BERBASIS PBL PADA MATERI MOMENTUM DAN IMPULS DI SMA YPPK TERUNA BAKTI JAYAPURA - Borotian, Sri Rahayu; Budiarti, Indah Slamet; Lumbu, Albert (Universitas Cenderawasih, 2023)
Associated with the development of teaching materials that adapt changes to the old curriculum into the new curriculum, namely the 2013 curriculum using a learning model, a PBL-based module will be developed. The PBL model is one model that can play a role in problem solving for students so that students can learn independently. The purpose of this study was to see the feasibility and responses of students to PBL-based modules. This researcher which was adapted from the ADDIE development model was only limited to the development stage so that this research was carried out in 3 stages, namely Analysis, Design, and Development which were limited to limited trials. The validation of the module was carried out by 4 validators to test 6 aspects which were assessed to obtain an overall percentage of 89.1% with a very good interpretation and limited trials were carried out to 31 students of class X IPA 2 where seen from the 4 aspects that were assessed to obtain an overall percentage of 88, 2% with very good implementation. It can be concluded that the PBL-based module on momentum and impulse class X material at SMA YPPK Teruna Bakti Jayapura is very appropriate to use and the response of students to PBL-based modules on momentum and impulse material for class X at SMA YPPK Teruna Bakti Jayapura is very good